2016
DOI: 10.4172/2161-0983.1000183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Constant Temperature on the Life Cycle of a Fly of Forensic Importance Lucilia cuprina

Abstract: Lucilia cuprina is one of the forensically important Calliphoridae fly. L. cuprina is a helpful resource at the crime scenes as well as a nuisance to sheep. It is known to be one of the first flies to occupy a corpse upon its death. Due to this, it has great importance in forensic field to find out post-mortem interval. In this study, the development of L. cuprina is studied in an incubator at different constant temperatures. Larvae of the L. cuprina were reared in an incubator at 20 º C, 25 º C, 30 º C, 35 º … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Also Lucilia maggots were recorded negatively correlated with temperature and positively with humidity. This result is disagreed with Bansode et al, (2016) who found that the development rate of the L. cuprina was slow at low temperature and fast at high temperature.…”
Section: Discussioncontrasting
confidence: 88%
“…Also Lucilia maggots were recorded negatively correlated with temperature and positively with humidity. This result is disagreed with Bansode et al, (2016) who found that the development rate of the L. cuprina was slow at low temperature and fast at high temperature.…”
Section: Discussioncontrasting
confidence: 88%
“…Studies have shown that insect development is directly related to environmental data such as temperature and humidity. Degree day model using development data of necrophagous insect on the carcass particularly first colonizers and environmental data such as temperature can be estimate the time of death (Kumara et al, 2017;Bansode et al, 2016;Chua, 2013). As a microhabitat, the corpse is used differently by the insects that colonize the body.…”
Section: Introductionmentioning
confidence: 99%
“…and humidity during the seasonal presence of the insect, it has been shown from Table (6) that the average temperatures ranged between 7.11-13.8oM and relative humidity be-tween 51.43-61.14 / R.H, The highest average insect density in the period from the first week of December 2018 to the fourth week of January 2019 was 38.25 insects recorded in the first week of December, an average temperature of 13.8o C and relative humidity 51.43%.Where, no insect infection was recorded in most of the readings in January for the second compatibility with the average temperature ranged from 7.11-8.76 C°, so it was found from the correlation that it was a high positive between the mean temperature and the average insect population density of (0.841) at a significant level p>0.0001 Where the correlation between humidity and insect density was negative (0.41-), and this is consistent with what [2] mentioned about the existence of a moral relationship be-tween preparing an insect from poplar leaves Chaitophorus eupharticus, temperature and significant, with relative humidity. Seventh: Seasonal presence of Cypsonoma hapalosarea in the autumn season 2018-2019: The symptoms of this insect appeared in very few numbers in the third week of December 2018, where in Table (7), with an average of 0.33 insects on both the northern and eastern sides, and rose in the first week of January 2019, with averages of 0.67 insects on both the northern and southern sides Eastern and the highest infection on the southern side showed an average of 1.0 insects in the second week of January. It appears from Table (7) that the highest average was 0.29 insects on the northern side and with a total of (7) insects and that the highest average recorded in the first week of January for the second with an average of (0.59) and a total of 7 insects.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Seventh: Seasonal presence of Cypsonoma hapalosarea in the autumn season 2018-2019: The symptoms of this insect appeared in very few numbers in the third week of December 2018, where in Table (7), with an average of 0.33 insects on both the northern and eastern sides, and rose in the first week of January 2019, with averages of 0.67 insects on both the northern and southern sides Eastern and the highest infection on the southern side showed an average of 1.0 insects in the second week of January. It appears from Table (7) that the highest average was 0.29 insects on the northern side and with a total of (7) insects and that the highest average recorded in the first week of January for the second with an average of (0.59) and a total of 7 insects.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation